Development of Rural Space in post-Communist Southeast Europe after 1989: A Comparative Analysis - Jordan, Peter (Journal for Geography, 2009)
This paper investigates the reasons for the current state of rural space in Southeast Europe, as well as its current structure. It is confirmed that pre-Communist structures, as well as divergent Communist systems and policies, contributed as much to current structures as have divergent post-Communist approaches and developments. Thus, we meet today very different situations in the rural space of Yugoslavian successor states on the one hand, and of other post-Communist countries of Southeast Europe with a planned economy (Romania, Bulgaria and Albania) on the other. But even the countries of former Yugoslavia show many divergences, mainly due to divergent demographic development in the wake of the Yugoslavian dissolution wars.
Keywords: structure of rural space; communist systems; transformation; agricultural policies; Southeast Europe